Labor market polarization and the absence of decent work for young people in Colombia - Calle Espinosa, Yhelin Cristina (2013)
This article aims to approach the phenomenon of polarization of labor income, taking into account the type of contract and employment stability, in order to represent the working conditions that young people between 16 and 25 years face in Colombia. First we present a review of reports about current working conditions, followed by an explanation of the concept of polarization; then we perform cluster analysis, which concludes that young people in the age range 16-25, are on average less paid per hour worked, and their situation is even more precarious if they do not have a written contract or if they have less than twelve months working in the same place.